Transcatheter Arterial Chemoembolization of Hepatocellular Carcinoma: Usefulness of Coded Phase-Inversion Harmonic Sonography - Minami, Yasunori; Kudo, Masatoshi; Kawasaki, Toshihiko; Kitano, Masayuki; Chung, Hobyung; Maekawa, Kiyoshi; Shiozaki, Hitoshi (American journal of roentgenology (1976), 2003)
The purpose of our study was to assess the value of coded phase-inversion harmonic sonography performed approximately 1 week after the patients had undergone transcatheter arterial chemoembolization with iodized oil for hepatocellular carcinoma. We studied 40 patients with 44 nodules measuring 1.5-11.0 cm in diameter (mean +/- SD, 3.9 +/- 2.0 cm) who underwent transcatheter arterial chemoembolization. Coded phase-inversion harmonic sonography, a technique based on a combination of phase-inversion harmonics and coded technology, was performed with a contrast agent approximately 1 week after chemoembolization. The results were compared with those obtained using dynamic CT (n = 44 lesions) and dynamic MR imaging (n = 20 lesions). We also evaluated the recurrence of hepatocellular carcinoma during clinical follow-up in 17 patients who did not undergo additional local therapy. The detection rates of intratumoral vascularity of coded phase-inversion harmonic sonography, dynamic CT, and dynamic MR imaging were, respectively, 38 (86%) of 44 lesions, 19 (43%) of 44 lesions, and 10 (50%) of 20 lesions. Of 19 nodules of hepatocellular carcinoma treated only by transcatheter arterial chemoembolization, 17 nodules showed enhancement on coded phase-inversion harmonic sonography, suggesting incomplete responses. In all 17 nodules, apparent recurrence was noted on dynamic CT during clinical follow-up, even in nodules that had been observed to be completely filled with iodized oil 1 week after the chemoembolization. We found coded phase-inversion harmonic sonography to be highly sensitive and accurate for evaluating the treatment response in patients with hepatocellular carcinoma even shortly after treatment. Consequently, it allows early recognition of the need for additional local ablation therapy and estimation of the risk of hepatocellular carcinoma recurrence.